National Society for Histotechnology and digital pathology association online self-paced digital pathology certificate of completion program - Elizabeth A Chlipala; Traci DeGeer; Kathleen Dwyer; Shelley Ganske; David Krull; Haydee Lara; Lisa Manning; Dylan Steiner; Lisa Stephens; Diane Sterchi; Aubrey Wanner; Connie Wildeman; et al. (Elsevier, 2019)
The field of digital pathology has rapidly expanded within the last few years with increasing adoption and growth in popularity. As digital pathology matures, it is apparent that we need well-trained individuals to manage our whole-slide imaging systems. This editorial introduces the joint National Society for Histotechnology and Digital Pathology Association online self-paced digital pathology certificate program which was launched in May 2018 that was established to meet this demand. An overview of how this program was developed, the content of the educational modules, and the way that this program is being offered is discussed.